Mechanical Characteristics of Linear Asynchronous Motor - Boudiaf, A.; Aissani, Z.; Bentriou, A. (Elektronika ir Elektrotechnika, 2011)
This work is concerned with the computations of the active forces in a unilateral linear asynchronous motor (LAM) without an inverse magnetic circuit, for both magnetic and unmagnetic moving bodies. Field and force computations were conducted and results analyzed. 1ll. 3, bibl. 4 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.279